Natural products against inflammation and atherosclerosis: Targeting on gut microbiota - Deng, Bing; Tao, Liyu; Wang, Yiru (Frontiers in Microbiology, 2022)
The gut microbiota (GM) has become recognized as a crucial element in preserving human fitness and influencing disease consequences. Commensal and pathogenic gut microorganisms are correlated with pathological progress in atherosclerosis (AS). GM may thus be a promising therapeutic target for AS. Natural products with cardioprotective qualities might improve the inflammation of AS by modulating the GM ecosystem, opening new avenues for researches and therapies. However, it is unclear what components of natural products are useful and what the actual mechanisms are. In this review, we have summarized the natural products relieving inflammation of AS by regulating the GM balance and active metabolites produced by GM.